Penerapan Two Step Cluster untuk Mengklasifikasikan Desa di Kabupaten Madiun Berdasarkan Data Potensi Desa - Alif Supandi; Asep Saefuddin; Itasia Dina Sulvianti (Xplore: Journal of Statistics, 2021)
Village development is a fundamental part of national development. Developing villages requires information on society necessities. This research aims at clustering villages in Kabupaten Madiun which has similar characteristics among each other and identify characteristics of the built clusters. Therefore, specific problems in the clusters of villages may become the foundation to implement development. The method that used for grouping objects with combined variables is two-step cluster. This analysis was used 14 variables consist of six categorical variables and eight numerical variables. The clustering analysis produces four clusters. The clusters that need more attention to be developed was Cluster 2 which had minimum facilities and resources. The average Silhouette coefficient for the clusters built was 0.3 which can be considered as fair category.